The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1074/jbc.m414138200
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of Sphingolipid Biosynthesis Abrogates the Signaling of Mss4, Phosphatidylinositol-4-phosphate 5-Kinase, in Yeast

Abstract: The functional relationships between phosphoinositides and sphingolipids have not been well characterized to date. ISP-1/myriocin is a potent inhibitor of sphingolipid biosynthesis and induces severe growth defects in eukaryotic cells because of the sphingolipid deprivation. We characterized a novel multicopy suppressor gene of ISP-1-mediated cell death in yeast, MSS4. MSS4 encodes a phosphatidylinositol-4-phosphate 5-kinase that synthesizes phosphatidylinositol (4,5)-bisphosphate (PI4,5P 2 ). We demonstrate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 57 publications
3
48
1
Order By: Relevance
“…During myriocin treatment, TORC2 activity is increased, whereas Rom2 activity is decreased. Consistent with this notion, Rom2 localization at the plasma membrane is diminished during myriocin treatment (48). This suggests that cells use the reciprocal regulation of both signaling systems to fine-tune communication on the state of the plasma membrane.…”
Section: Discussionsupporting
confidence: 71%
“…During myriocin treatment, TORC2 activity is increased, whereas Rom2 activity is decreased. Consistent with this notion, Rom2 localization at the plasma membrane is diminished during myriocin treatment (48). This suggests that cells use the reciprocal regulation of both signaling systems to fine-tune communication on the state of the plasma membrane.…”
Section: Discussionsupporting
confidence: 71%
“…Both mutants exhibited ,40% increase in PtdIns(4)P levels and a 30-40% decrease in PtdIns(4,5)P 2 levels (Fig. 5A). [ 3 H]inositol labeling was also carried out to determine if complex sphingolipid synthesis was perturbed, as previous studies have suggested that phosphatidylinositol phosphate levels are linked to complex sphingolipid levels (Audhya et al, 2004;Kobayashi et al, 2005;Bultynck et al, 2006;Daquinag et al, 2007;Berchtold et al, 2012). Using inositol labeling, similar results were observed with respect to increased PtdIns(4)P levels and reduced PtdIns(4,5)P 2 levels in the mss4 mutants.…”
Section: Induction Of the Flo11p Cell Adhesion Flocculin Is Reduced Isupporting
confidence: 52%
“…Mss4p is essential for cell viability and cells expressing kinase defective mutants are not viable (Kobayashi et al, 2005;Ling et al, 2012). Cells expressing the mss4-f12 mutant as the sole MSS4 copy were viable, suggesting that this mutant retained catalytic activity.…”
Section: Induction Of the Flo11p Cell Adhesion Flocculin Is Reduced Imentioning
confidence: 99%
See 1 more Smart Citation
“…These signaling events are mediated by PtdIns(4,5)P 2 -binding proteins (33)(34)(35). A recent study found that the plasma membrane localization of Mss4 is disturbed in ⌬csg2 cells (36), suggesting that accumulation of IPC-C or loss of MIPC causes mislocalization of Mss4.…”
Section: Discussionmentioning
confidence: 99%